2020
DOI: 10.3390/ma13194368
|View full text |Cite
|
Sign up to set email alerts
|

PlantCrystals—Nanosized Plant Material for Improved Bioefficacy of Medical Plants

Abstract: PlantCrystals are obtained by milling plant material to sizes <10 µm. Due to the disruption of the plant cells, active compounds are easily released, rendering the PlantCrystal technology an effective and low-cost process for the production of environmentally friendly plant extracts. The extracts can be used to produce phytomedicines, nutritional supplements or cosmetic products. Previous studies could already demonstrate the use of PlantCrystals to improve the antimicrobial or antifungal activity of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(64 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…The PlantCrystal technology is a simple method to produce ecofriendly and sustainable plant extracts [ 5 ]. The process does not require organic solvents and can be scaled up easily.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PlantCrystal technology is a simple method to produce ecofriendly and sustainable plant extracts [ 5 ]. The process does not require organic solvents and can be scaled up easily.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that PlantCrystals, i.e., nanosized plant materials, are a novel formulation strategy to increase the solubility and potential of plant molecules and this has already been proved for many different plants in previous studies [ 3 , 4 , 5 , 6 ]. PlantCrystals are composed of plants, parts of plants or plant wastes and can be produced by different wet milling methods, i.e., bead milling or high-pressure homogenization [ 5 ]. The particle size of PlantCrystals is below 10 µm, which ensures the complete destruction of all intact plant cells leading to more efficient extraction of the plant material without the use of organic solvents ( Figure 1 ) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations